AB0182 In vitro characterization of dermal fibroblasts from systemic sclerosis patients. (15th June 2017) - Brizzolara, R; Montagna, P; Soldano, S; Trombetta, AC; Ruaro, B; Sulli, A; Scabini, S; Stratta, E; Smith, V; Cutolo, M
Abstract : Background: Systemic sclerosis (SSc) is characterized by progressive fibrosis of the skin and/or internal organs. Skin fibrosis is mainly due to the excessive production of extracellular matrix (ECM) proteins from dermal activated fibroblasts. The high amounts of transforming growth factor-beta (TGFbeta) production induce fibroblast proliferation and their transition into profibrotic myofibroblasts. Consequently, the increased presence of alpha-smooth muscle actin (alpha-SMA)-positive myofibroblasts in affected tissues is associated with fibrotic tissue remodelling, that characterize SSc [1–4]. Objectives: To characterize dermal fibroblasts from SSc patients by evaluating the gene expression of specific phenotypic and profibrotic markers: fibrillar collagen type I (COL I), fibronectin (FN), fibroblast-specific protein 1 (S100A4), TGFbeta and alpha-SMA (marker of myofibroblasts). Methods: Human dermal fibroblasts were obtained by skin biopsy from affected areas of 6 active lcSSc patients after written informed consent and approval of medical ethics committee. SSc patients fulfilled the new EULAR/ACR criteria for SSc and they were treated only with various vasodilators (no severe clinical SSc complications were present at the time of skin sampling). Human SSc dermal fibroblasts were cultured up to 80% of confluence and at the third to fifth subpassages were used for experiments. Total RNA was extracted and quantitative real-time PCR (qRT-PCR) was performed to evaluate the gene expression of relevant fibroblast markers: COL I, FN, S100A4, TGFbeta and alpha-SMA. Results: In human SSc fibroblasts the gene expression of the relevant markers COL I, FN and S100A4 resulted of 10 7 RNA copies for each gene. Interestingly, in the same tested fibroblasts, the profibrotic alpha-SMA gene expression (marker of myofibroblasts) was similarly found highly expressed, with a result of 10 7 gene copies. On the contrary, TGFbeta showed a much lower gene expression (10 3 copies) compared to the other investigated genes. Conclusions: In human SSc cultured dermal fibroblasts, the gene expression of ECM proteins (COL I and FN), was found associated with a relevant gene expression of S100A4 and alpha-SMA, confirming their myofibroblast phenotype, as highly differentiated. Interestingly, TGFbeta gene appears to be less expressed. It could be concluded that myofibroblasts from the SSc skin mainly undergo the effects of the tissutal TGFbeta, since it seems that they do not contribute to its further production once differentiated. References: Cutolo M. et al. J Rheumatol 2015;42:3. Brunasso A.M. et al. F1000Research 2016;5:723. Hinz B et al. Am J Pathol 2012;180:1340–55. Dumoitier N. et al. Arthritis Rheumatol 2016 [Epub ahead of print]. Disclosure of Interest: None declared